Reliability and validity of the self-report version of the apathy evaluation scale in first-episode Psychosis: Concordance with the clinical version at baseline and 12 months follow-up. (September 2018) - Faerden, Ann; Lyngstad, Siv Hege; Simonsen, Carmen; Ringen, Petter Andreas; Papsuev, Oleg; Dieset, Ingrid; Andreassen, Ole A; Agartz, Ingrid; Marder, Stephen R; Melle, Ingrid
Highlights: Self-reporting of apathy for patients with psychosis is in concordance with clinician ratings. Patients with schizophrenia reported higher levels of apathy than other diagnostic groups. Controlling for level of depression altered some results. Abstract: Negative symptoms have traditionally been assessed based on clinicians' observations. The subjective experience of negative symptoms in people with psychosis may bring new insight. The Apathy Evaluation Scale (AES) is commonly used to study apathy in psychosis and has corresponding self-rated (AES-S) and clinician-rated (AES-C) versions. The aim of the present study was to determine the validity and reliability of the AES-S by investigating its concordance with the AES-C. Eighty-four first-episode (FEP) patients completed the shortened 12-item AES-S and AES-C at baseline (T1) and 12 months (T2). Concordance was studied by degree of correlation, comparison of mean scores, and change and difference between diagnostic groups. The Positive and Negative Symptom Scale (PANSS) was used to study convergent and discriminative properties. High concordance was found between AES-S and AES-C at both T1 and T2 regarding mean values, change from T1 to T2, and the proportion with high levels of apathy. Both versions indicated high levels of apathy in FEP, while associations with PANSS negative symptoms were weaker for AES-S than AES-C. Controlling for depression did not significantly alter results. We concluded that self-rated apathy in FEP patients is in concordance with clinician ratings, but in need of further study.